2014
DOI: 10.5114/wo.2014.43803
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of PTEN, PI3K, MTOR, and KRAS expression and their clinical and prognostic relevance to differentiated thyroid carcinoma

Abstract: Aim of the studyImportant signalling pathways play fundamental roles in the pathogenesis of thyroid carcinoma (TC). PTEN, mTOR, PI3K-p85 and K-Ras are the principal factors involved in these signalling pathways. To immunohistochemically examine the expressions of PI3K, mTOR and PTEN in patients suffering from follicular TC, papillary TC or variants thereof, as well as to investigate KRAS mutations via PCR to determine their clinical and prognostic relevance to differentiated thyroid cancer.Material and methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 39 publications
(59 reference statements)
1
17
0
Order By: Relevance
“…Through surgery and radioactive iodine ablation, most PTC patients have a good prognosis; however, a significant proportion of patients have persistent or recurrent disease and suffer from frequent recurrences or even distant metastases, leading to an unfavourable outcome. A minority of these patients will die from thyroid cancer ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Through surgery and radioactive iodine ablation, most PTC patients have a good prognosis; however, a significant proportion of patients have persistent or recurrent disease and suffer from frequent recurrences or even distant metastases, leading to an unfavourable outcome. A minority of these patients will die from thyroid cancer ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…The gene for PTEN protein lie in chromosome 10q23.3 area. PTEN protein is expressed in numerous early embryonic tissues, such as kidney, stomach, central and peripheral nervous system tissue (28). The expression levels of PTEN in the early stage of thyroid tissue growth and in adults are relatively high.…”
Section: Discussionmentioning
confidence: 99%
“…The expression levels of PTEN in the early stage of thyroid tissue growth and in adults are relatively high. In normal human cells, PTEN participates in the regulation of numerous signal transduction pathways, including PTEN/PI3K/AKT, FAK /PI30C and MAPK (28). Through these pathways, PTEN is involved in the maintenance of normal and regulatory substance metabolism and stabilization of the internal environment (29).…”
Section: Discussionmentioning
confidence: 99%
“…PTEN inactivation reflected by complete absence of PTEN by IHC was seen in 24.5% of our PTC cohort. Previous studies have reported differences in incidence of PTEN in different ethnic group which range from 29.7% ( Duman et al , 2014 ) in Caucasian to 52.6% in Asian population ( Min et al , 2013 ). Our results were similar to the Caucasian population as compared with other ethnicities.…”
Section: Discussionmentioning
confidence: 99%